Pathogenesis of respiratory failure in COVID-19 due to coagulopathy and endothelial dysfunction - T. O. Burdienko (Acta Biomedica Scientifica, 2024)
Respiratory failure is known to be the main clinical manifestation of COVID-19. However, the mechanism of its development has not been sufficiently studied. The originality of the study is that for the first time, coagulation, fibrinolysis and endothelial dysfunction indicators were studied depending on the SpO2/FiO2 index in patients with COVID-19.The aim of the work. To assess the role of impaired activity of the blood coagulation system and the development of endothelial dysfunction in patients with COVID-19 in the pathogenesis of respiratory failure.Methods. The study included 134 patients infected with SARS-CoV-2 virus having varying severity of the clinical picture. They were divided into three groups according to the SpO2/FiO2 index. We determined the number of venous blood cells and studied the level of transferrin (TF), D-dimer, tissue-type plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), inter-cellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) in the blood serum.Results. The study revealed that the tissue factor content increased by 24 % in patients of the third group compared to the first. The PAI-1 level was high in the second group and significantly decreased in the third (p < 0.001). An increase in the D-dimer level was recorded in the second and third groups. The levels of ICAM-1 and VCAM-1 molecules increased significantly in the third group of patients (p = 0.021 and p = 0.028, respectively). A moderate positive correlation was found between the SpO2/FiO2 index and the VCAM-1 level (p < 0.001), a weak positive correlation with PAI-1 (p = 0.012), and a weak negative correlation with TF (p = 0.027).Conclusion. Respiratory failure in patients with COVID-19 is caused by disorders in the hemostasis and fibrinolysis systems, as evidenced by an increase in the level of tissue factor and D-dimer, “consumption” of tissue activator and plasminogen activator inhibitor. Developing endothelial dysfunction, accompanied by increased secretion of adhesion molecules, aggravates the pathogenesis of respiratory failure.